Wind Effects of Architectural Details on Gable-Roofed Low-Rise Buildings in Southeastern Coast of China. Issue 11 (November 2014) - Huang, Peng; Tao, Ling; Gu, Ming; Quan, Yong
Gable-roofed low-rise buildings with ridges, protruding gable walls and eaves gutters are usually found on the southeastern coast of China, which are often invaded by typhoons. The wind effects due to ridges, protruding gable walls and eaves gutters on low-rise buildings as well as the wind loads on the architectural details themselves have been studied through a series of wind tunnel tests. The mean block pressure coefficient and the negative peak block pressure coefficient on different roof regions were compared, and architectural details' single tap pressure coefficients and drag coefficients were investigated. The study shows that each of the architectural details reduces roof wind load impact to various extents, and their coexistence has a most significant effect on decreasing roof wind loads, up to the reduction of 56% on the 'Ru' windward region for the mean block pressure coefficient, and 47% and 45% on the 'C1' and 'C2' corner regions for the worst negative peak block pressure coefficient, respectively. The worst negative peak pressure at the interior surface of the architectural details occurs when the wind blows obliquely on the exterior surface of the architectural details. This condition leads to very large peak net pressure coefficients. The worst net pressure coefficients of the protruding gable wall, ridge and eaves gutter are about 18.0, 10.5 and 6.7, respectively. Finally, the drag coefficients on the architectural details were also examined, and the results are suitable for engineering application.